2021
DOI: 10.3390/ma14216651
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Calcination Temperature on the Phase Composition, Morphology, and Thermal Properties of ZrO2 and Al2O3 Modified with APTES (3-aminopropyltriethoxysilane)

Abstract: This paper describes the effect of calcination temperature on the phase composition, chemical composition, and morphology of ZrO2 and Al2O3 powders modified with 3-aminopropyltriethoxysilane (APTES). Both ceramic powders were modified by etching in piranha solution, neutralization in ammonia water, reaction with APTES, ultrasonication, and finally calcination at 250, 350, or 450 °C. The obtained modified powders were characterized using X-ray diffraction (XRD), Fourier transform infrared (FTIR) spectroscopy, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 34 publications
(60 reference statements)
1
26
0
Order By: Relevance
“…No functional groups that could originate from artificial saliva were identified, particularly phosphates and chlorides ( Table 4 ). Only the presence of nitrogen and silicon compounds from the APTES surface modification process was confirmed, which we have already observed in previous studies [ 23 ]. The observations from FTIR were related to the results from the EDS, which are shown in the table ( Table 8 ).…”
Section: Resultssupporting
confidence: 79%
See 1 more Smart Citation
“…No functional groups that could originate from artificial saliva were identified, particularly phosphates and chlorides ( Table 4 ). Only the presence of nitrogen and silicon compounds from the APTES surface modification process was confirmed, which we have already observed in previous studies [ 23 ]. The observations from FTIR were related to the results from the EDS, which are shown in the table ( Table 8 ).…”
Section: Resultssupporting
confidence: 79%
“…The samples were prepared as described in our previous studies [ 22 , 23 ]. Zirconia (ZRO-T6 IMERYS), alumina (Sumitomo, Sumicorundum AA-18) and 90 μm fraction of purified cenospheres (origin: GRES-2 Powerplant, Kazakhstan) were modified by a two-step process: (I) etching in piranha solution and (II) surface modification with APTES (3-aminopropyltriethoxysilane).…”
Section: Methodsmentioning
confidence: 99%
“…In this study, we comprehensively researched the preparation of raw CSs for surface modification by chemical methods for the preparation of a PA-12 composite for 3D printing by FDM. This work builds on our earlier experience [35,36]. Our main research motivation was to prepare a PCC for potential medical applications that is better than pure PA-12.…”
Section: Introductionmentioning
confidence: 97%
“…They may either impart increased wetting action of the polymer on the filler surface in polymer composites, increased blending of two polymers in polymer blends, or chemical bonding on the interface of the system components [ 9 ]. Nakonieczny et al reported on the effective ZrO 2 silanization with APTES (3-aminopropyltriethoxysilane) [ 10 ], while Mahdavi on silanization of ZnO with APTES and TPTMOS (3-thiopropyltrimethoxysilane) [ 11 ] and Li on Al 2 O 3 silanization with APTES, AEAPTES (N-(2-aminoethyl)-3-aminopropyltriethoxysilane) and MATMOS [ 12 ]. Vacche et al reported that application of APTES bearing protic aminofunctional group capable of interacting with polar fluoropolymer allowed for significant reduction of dielectric loss and increase of thermomechanical stability of BaTiO 3 /P(VDF-TrFE) composites [ 13 ].…”
Section: Introductionmentioning
confidence: 99%